Endoscopic Ultrasound-Guided Hepaticogastrostomy Is Effective for Repeated Recurrent Cholangitis after Surgery: Two Case Reports - Akihiro Matsumi; Hironari Kato; Yousuke Saragai; Sho Mizukawa; Saimon Takada; Shinichiro Muro; Daisuke Uchida; Takeshi Tomoda; Kazuyuki Matsumoto; Masaya Iwamuro; Shigeru Horiguchi; Yoshiro Kawahara; et al. (Case Reports in Gastrointestinal Medicine)
We report the cases of two patients who underwent endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) using metallic stents (MS) for recurrent cholangitis due to benign biliary stenosis. The patients had repeatedly undergone double-balloon endoscopy and anastomotic stenosis. Thus, EUS-HGS was performed. The procedures were successful, and placement of a covered metallic stent (C-MS) relieved cholangitis. The occurrence of cholangitis was subsequently considerably reduced. For patients with postoperative recurrent cholangitis, EUS-HGS with MS should be considered because of its efficacy and safety.